The Effect Of Need For Achievement On Entrepreneurial Intentions Through Self-Efficacy Of Smk Students - Antika, Dwi; Eryanto, Henry; Fadillah Fidhyallah, Nadya (CV RIFAINSTITUT, 2023)
This study aims to determine the effect of need for achievement on entrepreneurial intentions through self-efficacy as a mediating variable in class XI Students of SMK Negeri 9 Jakarta. This research method uses quantitative research methods and survei methods. The population of this study were students of SMK Negeri 9 Jakarta, totaling 718 students with an affordable population of 204 students. The technique of determining the sample using path analysis model. The model in this study uses a path analysis model. The analytical technique used in this study uses Structural Equation Modeling Partial Least Square (SEM-PLS) which is calculated using software SmartPLS version 4.0. The result showed that the need for achievement had a significant direct effect on entrepreneurial intentions, need for achievement had a significant direct effect on self-efficacy, self-efficacy had a significant direct efffect on entrepreneurial intentions, and need for acheivement had a significant indirect effect on entrepreneurial intentions through self-efficacy.